International Labor Standards and International Trade - Golub, Stephen (IMF Working Papers; Working Paper ;, 1997)
This paper reviews controversies regarding linkage of international trade and labor standards. Pressures for international harmonization of labor standards arise in the context of increased trade between countries with large disparities in wages, and also reflect the history of labor standards. A critical distinction is made between standards related to fundamental human rights and those related to employment conditions. The main conclusion is that trade sanctions to enforce labor standards should not be an option, but that international agreements on core labor standards, with voluntary compliance, may, apart from being worthwhile on ethical grounds, defuse calls for protection.